Discourses in interaction - Tanskanen, Sanna-Kaisa (Pragmatics & beyond ;, 2010)
The fourteen contributions in this collection come from different approaches in pragmatics, interactional linguistics, conversation analysis, discourse analysis and dialogue analysis; the name given to what is studied ranges from spoken language and conversation to interaction, dialogue, discourse and communication. What the articles have in common is a similar starting point: they are informed by a form of linguistic understanding which has emerged within what could be called the interactional turn. The materials investigated come from several different languages, representing a variety of in.